The mediating role of quality of life in the relationship between teachers' participation in physical activity and empathic and social self-efficacy - Turhan, Muhammed Ozkan; Arslanboga, Ramazan; Eroglu, Sultan Yavuz; Koc, Mustafa Can; Carneiro, Lara; Talaghir, Laurentiu-Gabriel; Berdila, Anamaria (Frontiers Media Sa, 2026)
Background There is no study in the literature examining whether quality of life plays a mediating role in the relationship between teachers' participation in physical activity and self-efficacy.Objective The aim of this study is to examine the mediating role of quality of life in the relationship between teachers' participation in physical activity and their perceived empathic and social self-efficacy.Methods The participants were between 23 and 40 years old, with a mean age of 29.3 +/- 7.79 years. As data collection instruments, the International Physical Activity Questionnaire-Short Form adapted into Turkish by & Ouml;zt & uuml;rk (2005), the Quality of Life of Employees Scale developed by Stamm (2005) and adapted into Turkish by Ye & scedil;il, Erg & uuml;n, Amasyal & imath;, Er, Olgun, and Aker (2010), and the Perceived Empathic and Social Self-Efficacy Scale developed by Di Giunta et al. (2010) and adapted into Turkish by Ak & imath;n and Ba & scedil;& ouml;ren (2015) were used. Construct validity of the scales was tested using confirmatory factor analysis, and the analyses were conducted via SPSS, AMOS, and the PROCESS Macro plugin.Results The results revealed moderate positive relationships between job satisfaction and both empathic and social self-efficacy.Conclusion Mediation findings indicated that quality of life (job satisfaction) played a significant mediating role in the relationship between physical activity and empathic self-efficacy, as well as in the relationship between physical activity and social self-efficacy.
Keywords: Empathic; Physical Activity; Self-Efficacy; Social; Teacher